Reading: a motivating and interactive process (2000)
This research was primarily intended for those who are professionally concerned with the teaching of a foreign language, and especially for those who consider reading to be one of the most important sources for developing comprehension and production processes. We wanted our students to develop reading strategies by means of meaningful and motivating stories. Meaningful, because interesting stories encourage them to improve, and motivating, because they open the doors to multiple possibilities, thereby reinforcing other abilities.